Preparation and Characterization of Polymer Electrolyte of Glycidyl Methacrylate-Methyl Methacrylate-LiClO4 Plasticized with Ethylene Carbonate - M. Imperiyka; A. Ahmad; S. A. Hanifah; M. Y. A. Rahman (International Journal of Polymer Science)
In the present investigation, we study the properties of the plasticized polyglycidyl methacrylate P(GMA) copolymerized with polymethyl methacrylate P(MMA)-LiClO4 polymer electrolyte prepared by solution casting technique. The electrolyte was characterized using impedance spectroscopy (EIS), Fourier transforms infrared (FTIR), cyclic voltammetry (CV), and X-ray diffraction (XRD). The conductivity was improved from 1.3×10−12 S cm−1 to 8.7×10−6 S cm−1 upon the addition of 25 wt.% LiClO4 salt into P(GMA-MMA). The conductivity was improved from 1.4×10−6 S cm−1 to 3.0×10−4 S cm−1 upon the addition of 80 wt.% EC into P(GMA-MMA)-LiClO4 The band that belongs to C–O–C is shifted farther than the band of C=O upon the addition of LiClO4 into P(GMA-MMA). The band of C–O–C stretching is shifted to lower wavenumber upon the addition of EC into P(GMA-MMA)-LiClO4. Upon the addition of EC into P(GMA-co-MMA), the intensity of the peaks decreases, implying the amorphous nature of the electrolyte increases with the concentration of the plasticizer. The electrolyte is electrochemically stable at 3.8 V, making it suitable for dye-sensitized solar cell application.